Sejarah Perkembangan Filsafat - Putra Imanuel Zega (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
History of the Development of Philosophy We can conclude that Philosophy, as a scientific discipline that questions the nature of existence, knowledge, values, and reality, has gone through a long journey and is full of revolutionary thoughts throughout human history. The development of this philosophy not only reflects changes in human views of the world, but also emerges as a response to intellectual challenges, social changes, and scientific developments that have occurred from time to time. The earliest period in the history of the development of philosophy is the philosophy of ancient Greece. In ancient Greece, philosophers such as Thales, Socrates, Plato, and Aristotle introduced fundamental questions about the universe, ethics, politics, and knowledge. They try to understand the universe and human place in it through reason and reason. After the Greek classical period, philosophy underwent changes during the medieval period. During this time, Patristic and Scholastic philosophy became dominant. Patristic philosophy is closely related to early Christian thought and the influence of Church Fathers such as St. Augustine. At the same time, Scholastic philosophy, influenced by the work of Aristotle, attempted to integrate philosophy with Christian theology. The next period in the history of philosophy is the Age of Enlightenment, during which philosophy underwent major shifts. Philosophers such as Descartes, Kant, and Voltaire advocated ideas of rationality, freedom, and scientific progress. They challenge traditional dogma and authority and advance knowledge through rational thinking and the scientific method. The development of modern philosophy also includes schools such as German idealism led by figures such as Kant, Hegel, and Schopenhauer. They focus on thinking about consciousness, ideals, and oneness in search of an understanding of reality. In the 19th and early 20th centuries, important schools such as empiricism and utilitarianism emerged. Philosophers such as John Locke, David Hume, and Jeremy Bentham stressed the importance of experience and utility as the foundations of knowledge and ethics. Then, pragmatism and the analytic school, pioneered by figures such as William James, Bertrand Russell, and Ludwig Wittgenstein, put forward the practical use of knowledge and language in achieving a better understanding. Contemporary philosophy involves various schools of thought. Schools such as phenomenology (Husserl), existentialism (Sartre, Camus), hermeneutics (Gadamer, Ricoeur), and structure.